2008
DOI: 10.1100/tsw.2008.112
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Associated Kidney Microcysts

Abstract: Long-term lithium therapy is associated with impairment in concentrating ability and, occasionally, progression to advanced chronic kidney disease from tubulointerstitial nephropathy. Biopsy findings in patients with lithium-induced chronic tubulointerstitial nephropathy include tubular atrophy and interstitial fibrosis interspersed with tubular cysts and dilatations. Recent studies have shown that cysts are seen in 33–62.5% of the patients undergoing lithium therapy. MR imaging is highly capable of defining r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
7
0
4
Order By: Relevance
“…Until the MRI publication by Farres et al 5 in 2003, which reported renal microcysts in 16 patients with chronic lithium nephropathy, radiographic findings had not been described for this condition. Aside from 2 additional MRI case reports, 8 , 9 a single online sonogram, and 2 online CT images, 10 , 11 our literature search failed to uncover any additional imaging information related to lithium nephropathy. Our study grew out of an observation in a single patient whose renal sonogram showed multiple tiny echogenic foci that initially were interpreted as tiny calcifications; on reimaging with the same 6‐MHz transducer but without harmonic imaging, this finding was more suggestive of posterior acoustic enhancement associated with microcysts (Figure 1 and and ).…”
Section: Discussionmentioning
confidence: 98%
“…Until the MRI publication by Farres et al 5 in 2003, which reported renal microcysts in 16 patients with chronic lithium nephropathy, radiographic findings had not been described for this condition. Aside from 2 additional MRI case reports, 8 , 9 a single online sonogram, and 2 online CT images, 10 , 11 our literature search failed to uncover any additional imaging information related to lithium nephropathy. Our study grew out of an observation in a single patient whose renal sonogram showed multiple tiny echogenic foci that initially were interpreted as tiny calcifications; on reimaging with the same 6‐MHz transducer but without harmonic imaging, this finding was more suggestive of posterior acoustic enhancement associated with microcysts (Figure 1 and and ).…”
Section: Discussionmentioning
confidence: 98%
“…Bei diesen Patienten finden sich oft insgesamt mehr als 60 Zysten, meist bilateral und insbesondere in den Regionen mit den stärksten fibrotischen und atrophischen Veränderungen (q Abb. 2, Fallbeispiel 2) [38]. Thoma Das Absetzen der Lithium-Therapie hat keinen kurzfristigen Effekt auf den Serum-Kalzium-Spiegel, da der Hyperparathyreoidismus in zwei Drittel der Fälle über Nebenschilddrüsenadeno-me und in einem Drittel der Fälle über eine polyglanduläre Hyperplasie hervorgerufen wird [20].…”
Section: Lithium-induzierte Nephropathie ▼unclassified
“…L'imagerie par résonance magnétique (IRM) permettrait d'évaluer l'importance de l'atteinte rénale ou du moins d'affirmer la présence d'une néphropathie chronique au lithium [24,25]. L'aspect histologique est celui d'une fibrose interstitielle avec atrophie tubulaire, associée à une infiltration inflammatoire, associée à la présence de kystes et de dilatations tubulaires [22,26].…”
Section: Toxicité Chronique Du Lithiumunclassified